2008
DOI: 10.1055/s-2008-1073173
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking on the Serum Level of Duloxetine

Abstract: Duloxetine is a dual acting antidepressant (selective serotonin and norepinephrine reuptake inhibitor). Existing data suggest that the advisable therapeutic serum level of duloxetine ranges between 20 and 80 ng/mL. In a naturalistic setting we determined duloxetine serum levels within a steady state in a sample of depressive inpatients by high performance liquid chromatography (HPLC). The mean serum levels in 28 patients at the time of the first TDM analysis were 52.0+/-67 ng/mL. Eight of the patients were smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…46,47 Serum levels of duloxetine were found to be significantly lower among smokers, and it was suggested to occur by CYP1A2 induction by the polycylic hydrocarbons found in cigarettes. 48 See Table 2 for a summary of CYP enzyme inducers and inhibitors relevant to pregnancy.…”
Section: Sri-drug Interactionsmentioning
confidence: 99%
“…46,47 Serum levels of duloxetine were found to be significantly lower among smokers, and it was suggested to occur by CYP1A2 induction by the polycylic hydrocarbons found in cigarettes. 48 See Table 2 for a summary of CYP enzyme inducers and inhibitors relevant to pregnancy.…”
Section: Sri-drug Interactionsmentioning
confidence: 99%
“…Low-dose treatment with the slowly reversible acetylcholinesterase inhibitor rivastigmine was chosen since we observed moderate but distracting nausea at comparatively low doses of the rapidly reversible acetylcholinesterase inhibitor galantamine in our earlier studies [8] . Rivastigmine is not noted to have pharmacokinetic interactions with other drugs or nicotine, resulting in a change of plasma concentrations, as it has been shown in smokers for several other drugs such as antipsychotics [5] and antidepressants [12] . Baseline conditions for tobacco consumption and tobacco craving were assessed two times on visit 1 and again on visit 2, at the end of the 4-weeks baseline period immediately before starting the intervention.…”
Section: Procedures and Measurementsmentioning
confidence: 96%
“…In fact, plasma levels of psychotropic drugs may differ from one subject to another due to interindividual variability [10]. Other factors, such as polypharmacy [7] or smoking, have been demonstrated to alter DLX pharmacokinetics; a study reported that smokers tend to show remarkably lower serum drug levels, and this has been correlated to induction of CYP1A2 by polycyclic hydrocarbons contained in tobacco smoke [11].…”
Section: Introductionmentioning
confidence: 98%